Telerehabilitation of Chronic Obstructive Pulmonary Disease Patients in a Tertiary Care Hospital in Western India: A 3-month Follow-up Study - T. K. Abins; Ravi Gaur; Nitesh Manohar Gonnade; Nagma Sheenam; Chinchu Kolakkanni; T. K. Adharshna; A. P. Sangeeth (Indian Journal of Physical Medicine & Rehabilitation)
Introduction: India grapples with a mounting chronic obstructive pulmonary disease (COPD) crisis driven by pervasive air pollution, especially from biomass burning. New Delhi’s classification as the capital with the worst pollution, with 35 other Indian cities in the global top 50, underscores the severity. COPD, the third-leading cause of global mortality, claimed 3.23 million lives in 2019, with a projected surge due to prevalent smoking and ongoing pollution. Domestically, COPD accounts for 9.5% of all deaths. Emphasizing the urgency of Sustainable Development Goal 3.4 to reduce mortality from non-communicable diseases, including chronic respiratory diseases, cost-effective pulmonary rehabilitation (PR), particularly telerehabilitation, emerges as a promising avenue for comprehensive COPD management in this challenging landscape. Methods: Patients with COPD (gold stages 1–3) confirmed by pulmonary function tests were enrolled. Functional exercise capacity, dyspnoea levels and health-related quality of life (HRQoL) were assessed using the 6-min walk test (6MWD), modified Medical Research Council (mMRC) dyspnoea scale and SGRQ-C questionnaire, respectively. Participants received home-based PR and attended one 2-h PR session 3 days a week for 12 weeks. Follow-up was conducted telephonically monthly, and a final assessment was done at the end of the 3rd month. Results: Of the 88 initially recruited patients, 26 were lost to follow-up, leaving 62 who completed the 3-month programme. Significant improvements were observed in exercise tolerance (6-min walk test [6MWD]), with mean values increasing from 383.00 ± 71.22 to 441.3 ± 87.3 (P < 0.001). HRQoL, assessed by SGRQ-C, showed an overall improvement, with statistically significant reductions in total scores (42.15 ± 3.52–39.54 ± 3.41, P < 0.001) and in each domain (symptom, impact and activity). Conclusion: The study affirms telerehabilitation’s efficacy in enhancing exercise capacity and improving the quality of life for COPD patients, advocating its integration, particularly in regions with limited access to conventional rehabilitation programmes.